(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
Enzymes are highly specialized biological catalysts that accelerate biochemical reactions in living cells. They are essential components of cellular metabolism and ensure the continuous and balanced progression of metabolic processes. The catalytic efficiency of enzymes is closely related to their structural organization and chemical composition.